Development of CW and passively Q-switched DPSS laser - Gu, Jianhui. (2008)
In this project, research has been done on DPSS lasers by designing and finally fabricating a high-power DPSS laser based on theoretical analysis and detailed design calculations, and to acquire a thorough understanding of passive Q-switching of DPSS lasers using a GaAs wafer as a saturable absorber as well as an output coupler.